Predictors of response, progression‐free survival, and overall survival using NANT Response Criteria (v1.0) in relapsed and refractory high‐risk neuroblastoma. Issue 5 (19th January 2018) - Villablanca, Judith G.; Ji, Lingyun; Shapira‐Lewinson, Adi; Marachelian, Araz; Shimada, Hiroyuki; Hawkins, Randall A.; Pampaloni, Miguel; Lai, Hollie; Goodarzian, Fariba; Sposto, Richard; Park, Julie R.; Matthay, Katherine K.
Abstract: Purpose: The New Approaches to Neuroblastoma Therapy Response Criteria (NANTRC) were developed to optimize response assessment in patients with recurrent/refractory neuroblastoma. Response predictors and associations of the NANTRC version 1.0 (NANTRCv1.0) and prognostic factors with outcome were analyzed. Methods: A retrospective analysis was performed of patients with recurrent/refractory neuroblastoma enrolled from 2000 to 2009 on 13 NANT Phase 1/2 trials. NANTRC overall response integrated CT/MRI (Response Evaluation Criteria in Solid Tumors [RECIST]), metaiodobenzylguanidine (MIBG; Curie scoring), and percent bone marrow (BM) tumor (morphology). Results: Fourteen (6.9%) complete response (CR) and 14 (6.9%) partial response (PR) occurred among 203 patients evaluable for response. Five‐year progression‐free survival (PFS) was 16 ± 3%; overall survival (OS) was 27 ± 3%. Disease sites at enrollment included MIBG‐avid lesions (100% MIBG trials; 84% non‐MIBG trials), measurable CT/MRI lesions (48%), and BM (49%). By multivariable analysis, Curie score of 0 ( P < 0.001), lower Curie score ( P = 0.003), no measurable CT/MRI lesions ( P = 0.044), and treatment on peripheral blood stem cell (PBSC) supported trials ( P = 0.005) were associated with achieving CR/PR. Overall response of stable disease (SD) or better was associated with better OS ( P < 0.001). In multivariable analysis, MYCN amplification ( P = 0.037) was associated with worse PFS; measurable CT/MRI lesions ( P = 0.041) were associated with worse OS; prior progressive disease (PD; P < 0.001/ P < 0.001), Curie score ≥ 1 ( P < 0.001; P = 0.001), higher Curie score ( P = 0.048/0.037), and treatment on non‐PBSC trials ( P = < 0.001/0.003) were associated with worse PFS and OS. Conclusions: NANTRCv1.0 response of at least SD is associated with better OS in patients with recurrent/refractory neuroblastoma. Patient and tumor characteristics may predict response and outcome. Identifying these variables can optimize Phase 1/2 trial design to select novel agents for further testing.